2020
DOI: 10.3989/scimar.04991.29a
|View full text |Cite
|
Sign up to set email alerts
|

Sponges from rhodolith beds surrounding Ustica Island marine protected area (southern Tyrrhenian Sea), with a comprehensive inventory of the island sponge fauna

Abstract: The sponge fauna colonizing rhodolith beds from Ustica Island marine protected area was studied. Moreover, an inventory of the sponge species present along the island’s coasts was carried out for the first time. Analysis of rhodoliths trapped in nets used by local fishermen at two sites and data obtained from underwater video images were used to identify 25 sponge taxa, 22 of them at species level. The classes Demospongiae and Homoscleromorpha were present with 24 and 1 species, respectively. Most of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…maiteae (Santos et al, 2016), and several endemic coral (Cavalcanti et al, 2013;Pereira-Filho et al, 2015Amado-Filho et al, 2016;Negrão et al, 2021) and fish species (Moura et al, 2021). In the Mediterranean, the endemic deep-water kelp Laminaria rodriguezii (Barbera et al, 2003) and several species of endemic sponges (Longo et al, 2020) can be found on rhodolith beds, while in the NE-Atlantic the rare kelp L. ochroleuca and several rare rhodolith-associated seaweeds have been recorded (Peña et al, 2014;Braga-Henriques et al, 2022;Helias and Burel, 2023). At Cocos Island, Costa Rica, a new and endemic octocoral species, Rhodolitica oculta, has been found in association with rhodoliths (Breedy et al, 2021).…”
Section: Uniqueness or Raritymentioning
confidence: 99%
“…maiteae (Santos et al, 2016), and several endemic coral (Cavalcanti et al, 2013;Pereira-Filho et al, 2015Amado-Filho et al, 2016;Negrão et al, 2021) and fish species (Moura et al, 2021). In the Mediterranean, the endemic deep-water kelp Laminaria rodriguezii (Barbera et al, 2003) and several species of endemic sponges (Longo et al, 2020) can be found on rhodolith beds, while in the NE-Atlantic the rare kelp L. ochroleuca and several rare rhodolith-associated seaweeds have been recorded (Peña et al, 2014;Braga-Henriques et al, 2022;Helias and Burel, 2023). At Cocos Island, Costa Rica, a new and endemic octocoral species, Rhodolitica oculta, has been found in association with rhodoliths (Breedy et al, 2021).…”
Section: Uniqueness or Raritymentioning
confidence: 99%
“…The branches morphotype is associated with L. corallioides, P. calcareum, L. minervae, L. stic-taeforme, and L. racemus. The most associated fauna of the Italian calcareous algae beds include sponges, bryozoans, hydrozoans, polichaetes, molluscs, amphipods, gastropods, and echinoderms [24,25,[28][29][30][31]35,36].…”
Section: Coralline Algae Beds In the Italian Seasmentioning
confidence: 99%
“…The analysis of all the reported sites (Table 1) has also permitted an assessment of the main anthropogenic impacts affecting the Italian sites hosting coralline algae beds [25,30,40,43,45]. These impacts are mainly represented by litter (plastic, grass, wood, and metal objects) and by evidence of fishing activities (trawl marks and ghost net, longlines, lines, ropes, other fishing-related debris).…”
Section: Coralline Algae Beds In the Italian Seasmentioning
confidence: 99%
See 1 more Smart Citation
“…shell fragments or rocks). They are distributed worldwide and can be found at tropical (Amado‐Filho et al, 2012; Costa et al, 2020; Moura et al, 2021), temperate (Foster et al, 1997; Steller et al, 2003; Hinojosa‐Arango & Riosmena‐Rodríguez, 2004; García et al, 2014; Bracchi et al, 2019; Bracchi et al, 2022; Chimienti et al, 2020; Longo et al, 2020; Rendina et al, 2020; Romagnoli et al, 2021), and polar (Konar, Riosmena‐Rodriguez & Iken, 2006; Teichert et al, 2014; Ward et al, 2021) latitudes.…”
Section: Introductionmentioning
confidence: 99%